NEGARA HUKUM INDONESIA BERDASARKAN ANALISIS YURIDIS NORMATIF TENTANG UNSUR-UNSURNYA - Zakir, Fauzan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The state view or state theory of a nation cannot be separated from a nation's outlook on life. This nation's view of life is what causes other nations' views of the state. Looking at the existing theories in state science, we will find 3 (three) types of human views on state life, namely: a) Individualistic state view, from this group several famous thinkers are known, such as Thomas Hobbes, John Locke and Jean Jaques Rousseau. b) The group state view according to class theory, this was put forward by Marx, Engels and Lenin. The term